Multiple metal-bound oligomers from Ir-catalysed dehydropolymerisation of H3B center dot NH3 as probed by experiment and computation - Kumar, A; Johnson, H; Hooper, T; Weller, A; Algarra, A; Macgregor, SA (Royal Society of Chemistry, 2014)
Multiple metal-bound oligomers in the dehydropolymerisation of H 3B·NH3 have been observed by electrospray- ionisation mass spectrometry and NMR spectroscopy using the catalytic metal fragment {Ir(PCy3)2(H)2}+. A computational study suggests that sterics dictate whether multiple dehydrogenation/B-N coupling of amine-boranes H3B·NRR'H (R, R′ = Me or H) is observed, and also demonstrates the experimentally observed requirement for additional amine-borane to promote dehydrocoupling. This journal is © the Partner Organisations 2014.